1987
DOI: 10.1007/bf00284537
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic criteria of chronic left ventricular failure obtained during exercise-201Tl imaging

Abstract: Lung thallium fixation was studied during stress effort and redistribution in 39 patients with proven coronary artery disease (CAD) and in 11 control patients. The quantitative indices (Lung Stress Index (LSI), Lung Redistribution Index (LRI), and their ratio (LSI/LRI] were tested. The last one best correlated with left ventricular end diastolic pressure elevation and positive stress test. Detection of left ventricular failure was possible (sensitivity 80%, specificity 95%) using LSI and LSI/LRI. These indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A study by Wu et al[11] in 2003 reported that SPECT was only of modest value to distinguish between ischemic and idiopathic cardiomyopathy and concluded that SPECT cannot be relied upon in an individual patient to differentiate the two entities. Overall, the existing literature points to a high sensitivity for SPECT in CAD detection (nearly 100% in some published studies) while specificity on average is only about 40%-50% in LVD patients[12-15]. …”
Section: Discussionmentioning
confidence: 99%
“…A study by Wu et al[11] in 2003 reported that SPECT was only of modest value to distinguish between ischemic and idiopathic cardiomyopathy and concluded that SPECT cannot be relied upon in an individual patient to differentiate the two entities. Overall, the existing literature points to a high sensitivity for SPECT in CAD detection (nearly 100% in some published studies) while specificity on average is only about 40%-50% in LVD patients[12-15]. …”
Section: Discussionmentioning
confidence: 99%
“…The overlapping was quite small, resulting in good discriminative ability. The study by Bureau et al (1987) compared the initial study mean pulmonary counts/ mean myocardial counts in the brightest segment with the late study mean pulmonary counts/mean myocardial counts in the brightest segment in the initial study (! ); these results are difficult to compare with other work in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal changes in PM uptake ratios were considered in three studies (Kushner et al 1981 ;Lahiri et al 1984;Bureau et al 1987) with conflicting results and utilizing three different methods of assessment. Temporal changes in pulmonary T1 content were addressed in three studies (Bingham et al 1980;Kushner et al 1981;Levy et al 1983), all measuring T1 uptake in the upper left lung, without considering the possibility of variation between lung regions.…”
Section: Introductionmentioning
confidence: 99%
“…In a further study by Bureau et al (1987), the authors used a lung/heart ratio acquired immediately after stress, which they called the lung stress index (LSI). A similar index was used after the patient had rested for 3 h and was called the lung redistribution index (LRI).…”
Section: Increased Lung Uptake Of 2°1ti After Stress Testmentioning
confidence: 99%
“…Summary of major studies involving thallium-201 lung/ heart ratios 1980 Boucher et al 1981Kushner et al 1983Levy et al 1984Lahiri et al 1985Rothendler et al 1987Bureau et al 1987Gill et al 1988Kaul et al 1988Miller et al 1989Kahn et al 1990Mannting 1991Kurata et al 1991 Ilmer et al Summary of major studies involving thallium-201 lung/ heart ratios 1980 Boucher et al 1981Kushner et al 1983Levy et al 1984Lahiri et al 1985Rothendler et al 1987Bureau et al 1987Gill et al 1988Kaul et al 1988Miller et al 1989Kahn et al 1990Mannting 1991Kurata et al 1991 Ilmer et al…”
Section: Introductionmentioning
confidence: 99%